Optimizing LPSO phase to achieve superior heat resistance of Mg–Gd–Y–Zn–Zr alloys by regulating the Gd/Y ratios - Jianxin Zhou; Hong Yang; Jianfei Xiao; Bin Jiang; Xiaojun Luo; Wenlong Xie; Wei Li; Zhihua Dong; Jiangfeng Song; Junyao Xu; Guangsheng Huang; Dingfei Zhang; et al. (Journal of Materials Research and Technology, 2023)
The microstructural features of long period stacking ordered (LPSO) phase in Mg–(11-x)Gd–xY–1Zn–0.3Zr (wt.%) alloys were optimized by adjusting Gd/Y ratios to10:1, 8:3, 6:5, 4:7 and 2:9, respectively. Superior high-temperature strength was successfully obtained in the extruded 6Gd–5Y alloy with ultimate tensile strength (UTS) values of 338 MPa and 286 MPa at 250 °C and 300 °C, respectively. In the as-cast alloys, with the decrease of Gd/Y ratio, the type of intermetallic compound gradually changed from (Mg, Zn)3(Gd, Y) (W) to LPSO phase. After homogenization, the W phase was completely converted to LPSO phase except for the 10Gd–1Y alloy. Importantly, the block-shaped LPSO phases with the smallest size and the abundant lamellar LPSO phases were formed in the 6Gd–5Y alloy, which significantly influenced the microstructures of the extruded alloy. Firstly, the small sized block-shaped LPSO phase before extrusion provided favorable conditions for the formation of thin plate-shaped LPSO phase at DRXed regions, which effectively hindered the grain boundary migration at high temperature due to superior thermal stability. Secondly, the profuse lamellar LPSO phases prior to extrusion contributed to the highest density of low angle grain boundaries (LAGBs) and residual dislocations in the extruded 6Gd–5Y alloy, which obstructed dislocation slip at elevated temperatures. In addition, the abundant lamellar LPSO phase also caused the fine DRXed grain size and strong basal texture to enhance the high-temperature strength of the extruded 6Gd–5Y alloy.